2017
DOI: 10.2319/071117-464.1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of multiple impacted maxillary teeth in a hyperdivergent Class I patient using Temporary Skeletal Anchorage Devices and augmented corticotomy

Abstract: Treatment of multiple impacted teeth is challenging. Three-dimensional treatment planning can help in delivering a better outcome. This case report presents a patient with an incomplete dental transposition between the canine and lateral incisor of the maxillary right side associated with the impaction of a dilacerated right central incisor. Using a two-stage surgical exposure and augmented corticotomy, the patient's occlusion and smile esthetics were significantly improved, and Class I occlusal relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…Orthodontic traction of impacted teeth using orthodontic miniplate in the biocreative orthodontic strategy has several advantages when the patients are in mixed dentition. 9,10 First, stable skeletal anchorage prevents unwanted side effects to the adjacent teeth because no forces are applied to other teeth in the dentition. Moreover, the treatment period for applying a fixed appliance is greatly reduced, which helps to control oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthodontic traction of impacted teeth using orthodontic miniplate in the biocreative orthodontic strategy has several advantages when the patients are in mixed dentition. 9,10 First, stable skeletal anchorage prevents unwanted side effects to the adjacent teeth because no forces are applied to other teeth in the dentition. Moreover, the treatment period for applying a fixed appliance is greatly reduced, which helps to control oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…In the case presented here, a titanium orthodontic miniplate was inserted in the opposing arch to serve as stable skeletal anchorage. [7][8][9][10] This clinical report presents the recovery of impacted molars from a large dentigerous cyst treated with marsupialization and orthodontic traction using orthodontic miniplate. mandibular region was noted with no pain on palpation.…”
mentioning
confidence: 99%
“…In den letzten Jahren werden zunehmend Studien und Fallberichte publiziert, in denen Kieferorthopäden skelettale direkte oder indirekte Verankungsmechaniken zur Einordnung verlagerter Zähne einsetzten [28,33,34]. Wie bereits in einem früheren Fallbericht beschrieben, lassen sich mit diesen minimalistischen, relativ nebenwirkungsarmen Behandlungsmaßnahmen impaktierte Schneidezähne bestens einstellen [35].…”
Section: Diskussionunclassified
“…Kim et al78 reported that the tooth was moved to the desired position by performing a corticotomy and surgery to expose multiple impacted maxillary teeth. Karthikeyan et al79 treated a Class I malocclusion and open bite patient by removing the bulky anterior cortical bone and intruding the anterior teeth.…”
Section: Indications and Limitationsmentioning
confidence: 99%